Netizens of Rhetorical Strategy in Responding to President Prabowo Subianto's Political Policy Campaign on Budget Cuts - Helmin Maele; Muslimin; Puspita Dian Agustin (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the forms and identify patterns of netizens' rhetorical strategies in the comments section in response to President Prabowo Subianto's political campaign policy regarding budget cuts. This study uses a qualitative approach with a descriptive qualitative approach. The data analyzed consisted of public comments sourced from the KompasTV YouTube video titled "Prabowo Bluntly: Some Oppose Him Regarding Budget Cuts, Feeling Like a Little King!". Data collection techniques were carried out through reading techniques, documentation techniques, and purposive sampling techniques. The data analysis technique includes three stages: data reduction, data presentation, conclusion drawing and verification. The results of this study indicate that 55 netizens' rhetorical strategies were found, consisting of 2 Ethos (3.6%), 15 Pathos (27.3%), 8 Logos (14.5%), 24 Pathos + Logos combinations (43.6%), 2 Ethos + Pathos combinations (3.6%), and 4 Ethos + Pathos + Logos combinations (7.3%). These rhetorical strategies are demonstrated through the use of references to figures, personal experiences, emotional sentences, satire, rhetorical questions, and logical arguments. These findings indicate that netizens tend to combine emotional elements and logical reasoning when expressing their opinions regarding President Prabowo Subianto's budget cuts policy on digital media.